How Russian Doctoral Education Fulfills Its Main Mission: Scientometric Assessments (Article 2) - B. I. Bednyi; A. A. Mironos; N. V. Rybakov (Высшее образование в России)
Change management in the field of training and certification of academic personnel implies a reliable information support in the form of statistical and sociological data that enable the monitoring of the effectiveness of the institution of doctoral education. The current system for monitoring the activities of doctoral schools does not fully meet these requirements, thus making it difficult to assess objectively the implementation of doctoral education’s main function – the training of researchers and faculty for higher education. The article attempts to fill this information lacuna by presenting an analysis of the database created by the authors which contains information about the defense of dissertations and research results of PhD students who graduated in 2013 from nine Russian universities over the five-year period after their graduation (N = 1178). Information on the results of each graduate’s research activities was obtained from open sources: the portal of the Higher Attestation Commission, the electronic catalog of the Russian State Library, Scopus and eLibrary.ru databases, as well as the database of the Industrial Property Institute. As a result of our research, it was established that the actual timeframe of doctoral students’ advancement to their academic degree is determined by discipline-related factors. In the sample as a whole, the share of persons who defended their dissertations was 45% of the total number of graduates, which is 1.7 times higher than the share of graduates who defended their dissertations in the course of their studies at the doctoral school. Approximately 90% of graduates defend their dissertations no later than two years after graduation from the doctoral school. The quantitative data of doctoral school graduates’ retention in the academic field are given, with the breakdown by discipline. On average, more than 60% of Candidate of Sciences degree holders continue their careers in academic positions. The obtained data on Russian doctoral school graduates are in good agreement with the results of monitoring doctoral programs’ graduates in Europe and the USA. The results of this work make it possible to take a fresh look at the methodology for diagnosing the effectiveness of university doctoral schools.